Islamic Education Teachers' Strategies to Form Students' Discipline Character - Khoirunnisa, Nabila; Tumin (Journal of Islamic Education, 2025)
This study explains the role of Islamic Education teachers in efforts to shape the character of student discipline at SMP Muhammadiyah 1 Yogyakarta. This study aimed to determine the role of Islamic Education teachers in shaping the character of student discipline and the strategies used at SMP Muhammadiyah 1 Yogyakarta. This study is a qualitative descriptive study. The subjects of the study were teachers, students, and documentation. Data collection was carried out through observation, interviews, and documentation research. Analysis is conducted through three main stages, namely data reduction, data presentation, and conclusion. The study results found that Islamic Education teachers showed their roles as educators, motivators, and facilitators in shaping the character of student discipline through strategies based on Islamic values. Different from other studies that generally discuss discipline in a general context, this study highlights specific approaches such as the 3S habit (Sapa, Senyum, Salam), congregational dhuha and dzuhur prayers, and reading the Qur'an together as a method of forming positive habits. This approach instills academic discipline and builds order and good habits in students' daily lives. This study emphasizes the integration of Islamic values ​​in educational practices, making it more relevant in Islamic schools that seek to balance academic and character aspects. Thus, this study provides a unique contribution to understanding how the role of teachers and Islamic strategies can effectively shape student discipline while also adding insight into a more contextual pedagogical approach to Islamic education.